ANALISIS PENGARUH CELEBRITY ENDORSEMENT, ONLINE CUSTOMER REVIEW DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MELALUI E-COMMERCE DENGAN TRUST SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Somethinc di Kota Semarang) - Ika Kirana, Firda Rozza; Yoestini, Yoestini (Diponegoro Journal of Management, 2024)
ABSTRACT The development of technology in Indonesia has a major influence on economic development, one of which facilitates buying and selling activities by using e-commerce. Ecommerce helps consumers to buy products without having to come to the store directly and also helps companies to market their products. One company that markets its products through e-commerce is Somethinc. Somethinc produces a variety of products that are useful for overcoming facial, skin and hair problems. In the world of marketing celebrity endorsement is often used as a strategy to convince potential customers. In addition, online customer reviews and service quality also affect consumer confidence to buy the products offered. This research was conducted on 138 respondents who are Somethinc consumers in Semarang. The data collection technique uses non-probability sampling with purposive sampling where data is collected through the results of a google form questionnaire which has a Likert scale of 1-7. The data that has been collected is then analyzed using the Structural Equation Model (SEM) with the AMOS 24 analysis tool. The results showed that celebrity endorsement has a positive but insignificant effect on trust. In addition, it was found that online customer reviews and service quality have a positive and significant effect on trust. The results concluded that trust is unable to mediate celebrity endorsement on purchasing decisions. But trust mediates the influence between online customer reviews and service quality on purchasing decisions.